Management strategies and outcomes for very elderly patients with diffuse large B‐cell lymphoma. Issue 20 (28th June 2016) - Chihara, Dai; Westin, Jason R.; Oki, Yasuhiro; Ahmed, Mohamed A.; Do, Bryan; Fayad, Luis E.; Hagemeister, Fredrick B.; Romaguera, Jorge E.; Fanale, Michelle A.; Lee, Hun J.; Turturro, Francesco; Samaniego, Felipe; et al.
Abstract : BACKGROUND: The number of elderly patients with diffuse large B‐cell lymphoma (DLBCL) in our aging society continues to rise, although the optimal management of very elderly patients with DLBCL is unknown. METHODS: This study evaluated 207 patients who were 80 years old or older at the diagnosis of DLBCL from 2002 to 2014 at The University of Texas MD Anderson Cancer Center. Analyzed features included clinical characteristics, treatment outcomes, and tolerability of therapy. Cox proportional hazards models examined relations between the treatment regimen and survival. RESULTS: The median age was 83 years (range, 80‐96 years). Fifty‐four percent of the patients had intermediate‐ to high‐risk or high‐risk International Prognostic Index scores. Fifteen percent had scores of 4 or higher on the Charlson Comorbidity Index (CCI). The initial therapies included rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R‐CHOP; 70%); rituximab, etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (R‐EPOCH; 6%); and non–anthracycline‐based therapies, including rituximab, cyclophosphamide, etoposide, vincristine, and prednisone (R‐CEOP) and rituximab, cyclophosphamide, vincristine, and prednisone (R‐CVP; 10%). With a median follow‐up of 38.1 months, the 3‐year failure‐free survival (FFS) and overall survival (OS) rates were 55% and 54%, respectively. Eighty‐eight patients experienced relapse during the follow‐up, but only 3 patients (3.4%) experienced relapse beyond 3 years. Patients who received R‐CHOP or R‐EPOCH had significantly longer FFS than those who received R‐CEOP or R‐CVP, with 3‐year FFS rates of 63% for R‐CHOP, 74% for R‐EPOCH, and 23% for R‐CEOP and R‐CVP. Male sex, a monocyte count ≥ 500 × 10 7 /L, and a CCI score ≥ 4 were significantly associated with inferior OS. Extranodal disease (≥2) and a higher CCI score were associated with a high risk of treatment‐related mortality. CONCLUSIONS: With anthracycline‐based regimens such as R‐CHOP and R‐EPOCH, very elderly patients with DLBCL had superior outcomes similar to those achieved for younger patients with DLBCL. Cancer 2016;122:3145–51 . © 2016 American Cancer Society . Abstract : Very elderly fit patients (age ≥ 80 years) have survival outcomes similar to those of younger patients with standard‐dose anthracycline‐based regimens. Patient education and close monitoring with sufficient supportive therapy during treatment are imperative for preventing treatment‐related mortality.